Epidermal growth factor receptor mutation in adenocarcinoma lung in a North Indian population: Prevalence and relation with different clinical variables - Kasana, Basharat Ahmad; Dar, Waseem Raja; Aziz, Sheikh Aijaz; Lone, Abdul Rashid; Sofi, Najeeb Ullah; Dar, Imtiyaz Ahmad; Latief, Muzamil; Arshad, Faheem; Hussain, Moomin; Hussain, Mir (Indian Journal of Medical and Paediatric Oncology, 2016)
Introduction: Lung cancer is one of the most common causes of cancer deaths worldwide. Adenocarcinoma is taking over squamous cell lung cancer as the predominant histological subtype. Several cytotoxic drugs are available for the treatment of lung cancer, but side effects limit their use. Recently, targeted therapies for cancers have come into clinical practice. Aims and Objectives: To determine the prevalence of epidermal growth factor receptor (EGFR) mutation in adenocarcinoma lung in a North Indian population and its relation with different clinical variables. Materials and Methods: A total of 57 patients who met inclusion criteria were recruited into the study. Relevant history, clinical examination and investigations were done. EGFR mutation was done in all patients. Results: A total of twenty patients tested positive for EGFR mutation. EGFR was more frequently detected in female patients (53.8%), while as only 19.4% of the male patients expressed EGFR mutation, which was statistically very significant P = 0.007). EGFR mutation was more frequently detected in nonsmokers (52%) as compared to smokers (21.9%) which also was statistically significant P value of 0.018). EGFR mutation was more common in Stage III and IV adenocarcinomas (48%) as compared to Stage I and II (21.4%) which was statistically significant P value 0.034). Conclusion: EGFR mutation should be routinely done in all patients of adenocarcinoma lung particularly non-smoker females with Stage III and IV disease.
Keywords: Adenocarcinoma lung; epidermal growth factor receptor; geftinib